Оборонні споруди монастирів оо. Бернардинів західної України у XVII–XVIII століттях - Хохонь, Михайло; Khokhon, Mykhailo (Видавництво Львівської політехніки, 2020)
У статті на основі камеральних та натурних досліджень проведено аналіз ландшафтного та містобудівного розташування монастирів оо. Бернардинів, розкрито раніше невідомі факти про існування та функціонування окремих монастирських фортифікаційних елементів, визначено особливості оборонних споруд ордену.

Reliable fortifications were the key to the stable functioning of the castle, city or monastery on the territory of Western Ukraine in the XVII–XVIII centuries. Monastic complexes dominated actively in the space of settlements or landscape. Bernardin Order monasteries were one of the most numerous among the orders of the Western rite. Nowadays there often arises the question of determining the historical boundaries of objects and the original architectural and compositional integrity of monastic complexes during the development of urban planning documentation and restoration projects. Bernardin Order monasteries were actively studied by Ukrainian and Polish scientists, such as V. Vuytsyk, O. Boyko, I. Somochkin, A. Bethley, M. Kurzey, E. Kvetsinska. Research focuses mostly on the sacred elements of the complexes and describes the historical and architectural aspects of the monuments. The fortifications were partially inspected or not mentioned at all. The purpose of the article is to collect, systematize and reveal new facts of functioning and formation history of the defensive structures of Bernardine Order monasteries in Western Ukraine. Also the the purpose is to determine the location, dimensions, architectural and planning features of the fortifications of monasteries. In the studied period, we can identify about 50 defense complexes of various orders of the Western Rite, located in or outside the downtown. Bernardine Order monasteries are among the most common and are represented in in Berezhany, Husiatyn, Dubno, Zbarazh, Izyaslav, Lviv, Leshniv, Sokal and Khrystynopil. The Order of Bernardines is a branch of the Franciscan order, which was formed in the XII century. The Order of Bernardines appeared in the territory of the Polish-Lithuanian Commonwealth and Western Ukraine in the middle of the 15th century. As a result of the study of nine monasteries of the Bernardine Order, it was found that the architecture of the Order is clearly traced in the construction of its own fortifications. The article identifies the influence of the urban planning factor on the configuration and dimensions of the defense lines of objects. The Bernardines owned some of the most powerful defensive monasteries in Western Ukraine: in Sokal, Izyaslav and Lviv. The monasteries of this order were mostly located in downtown. Three of them, namely in Berezhany, Dubno, Leshniv, were located in the corners of downtown near the gates. The monasteries in Lviv, Husiatyn and Khrystynopil, which were blocked to the corner of the city defensive walls from the outside allocated to a separate type. Monastery in Zbarazh was located in the middle of the defense line near the gate and had its own defense walls. At this stage, the study revealed one defensive monastery church – in Leshnev. The monasteries in Dubno and Brzezany were defended by powerful city fortifications. The fortifications of the monasteries in Lviv and Sokal should be singled out. The monastery in Lviv, due to the status of the city and responsibility, was committed to active defense, which explains the presence of a three-tiered tower, strong walls with a loophole and a ravelin at the entrance. The monastery in Sokal was an outpost of the territory and a powerful center of pilgrimage that resulted into its economical wealth. It was found that the Bernardine complexes used mostly newer forms of protection – bastions and ramparts.
Defense buildings of Bernardin’s order monasteries of western Ukraine in XVII–XVIII centuries
Keywords: оборонні споруди; монастир; оо Бернардинів; Західна Україна; fortifications; monastery; Bernardine order; Western Ukraine; 726.3 (477.4)